Unpacking the Understanding of Social Justice in Higher Education From the Perspectives of Educators in Law, Health and Social Work - Schiller, Ulene; Hlope, Yvette Nkondo; van Coller, Arthur; Singh, Shenuka; Moema, Esmey Baratwa Esther (International Journal of African Higher Education, 2025)
Social justice-informed pedagogy remains the bedrock for ensuring that educational programmes in higher education in South Africa are responsive to unmet learning needs and are contextualised within students' lived experiences. This paper documents the reflections of five senior academics (the authors) on how social justice can be applied to Law, Medicine, Dentistry, and Social Work, respectively. These academics were part of the Teaching Advancement at Universities (TAU) fellowship programme. Using Kim’s Critical Reflective Inquiry Model and Nancy Fraser’s concept of participatory parity, the authors interrogated the structural barriers to equitable education and the role of discipline-specific pedagogical practices in advancing or inhibiting social justice. Findings reveal that while social justice is a guiding principle across the identified disciplines, its implementation is inconsistent and often constrained by entrenched institutional norms and economic disparities. Legal education struggles to move beyond doctrinal teaching to cultivate critical consciousness; health sciences education largely embeds social justice in patient-centred care but overlooks the lived experiences of students; and social work education emphasises equity yet still faces structural barriers in practice-based learning. The study highlights the necessity of embedding participatory parity in higher education and fostering an emancipatory pedagogy that moves beyond content delivery to active student engagement. The paper concludes with recommendations for higher education institutions to institutionalise social justice principles through curriculum reform, inclusive teaching strategies, and structural changes that promote equal access and participation.